ANGIOSPERMIC MEDICINAL PLANTS DIVERSITY OF GRAMBHARTI (AMARAPUR) VILLAGE, MANSA TALUKA, GANDHINAGAR DISTRICT, GUJARAT, INDIA (International Association of Biologicals and Computational Digest, 2023)
The present study deals with the diversity of Angiospermic medicinal plants of Grambharti (Amarapur) village, in Gandhinagar district during January 2023 to March 2023. Information regarding medicinal uses and local name of plants was collected through direct field survey and personal interview with the locals and knowledgeable persons and cultivators. Then identify the plant species and arranged according to Bentham and hooker’s classification system and prepare herbarium sheets.A total 96 Angiosperm plant species belonging to 46 families are recorded, in which 38 species belonging to 23 families are medicinal plant species. They are used in different disease. The study indicates that the area is very rich in traditional knowledge and a great diversity of medicinal plants which are offer a convenient strategy for promoting cultivation and conservation of variety of Angiosperm medicinal plants.
Keywords: Angiosperm plants, Medicinal plants, Diversity, Grambharti (Amrapur)